Deep sleep predicts the cognitive evolution of mild‐moderate Alzheimer's disease patients. (31st December 2021) - Targa, Adriano; Benitez, Ivan David; Dakterzada, Faride; Minguez, Olga; Barbe, Ferran; Piñol‐Ripoll, Gerard
Abstract: Background: To investigate the association between sleep and the cognitive evolution of mild‐moderate Alzheimer's disease patients. Method: Observational, prospective, single‐center study, including consecutive patients diagnosed with mild‐moderate Alzheimer's disease (NCT02814045). The individuals were submitted to overnight polysomnography, followed by neuropsychological evaluations at baseline and after 12 months of follow‐up. Principal component analysis characterized the sleep architecture of the cohort into two main types: individuals with a propensity to deepen their sleep (deep sleepers) and individuals who spent most of the time in the lighter sleep stage (light sleepers). Result: The cohort included 125 subjects with a median [IQR] of 75.0 [72.0;80.0] years. The mean difference (95% CI) in the Mini‐mental state examination score at 12 months between deep and light sleepers was ‐1.51 (95% CI: ‐2.47 to ‐0.54; p‐value = 0.002). Accordingly, sleep depth and cognitive evolution presented a dose‐response relationship (p‐for‐trend = 0.02). Regarding the specific cognitive subdomains, we observed differences related to the processing speed, demonstrated by the Stroop words test (‐1.48; 95% CI: ‐2.58 to ‐0.38; p‐value = 0.009), and to the executive function, demonstrated by the Verbal fluency test (‐1.70; 95% CI: ‐2.85 to ‐0.55; p‐value = 0.004). Conclusion: Considering that light sleepers presented an increased cognitive decline, the sleep profile may have a predictive role in the cognitive evolution of mild‐moderate Alzheimer's disease patients. The modifiable nature of sleep sets this behavior as a possible useful intervention for the improvement of cognitive evolution.